Design Application GM3-Bacterial© Application Based on Android Smartphone for Bacterial Identification - Megahati S, Ruth Rize Paas; Azhar (RADINKA JAYA UTAMA PUBLISHER, 2022)
Digital technology continues to develop along with the times, such as Android smartphones. Android smartphones are a new innovation in the identification of bacteria carried out in the Microbiology and Biotechnology Laboratory. Identification of bacteria in the Microbiology and Biotechnology laboratory is usually done manually using various substances, is expensive, has to do a lot of tests, and has to grow bacteria in vitro in a growth medium. In addition, the inaccuracy of the results of bacterial identification if the bacteria tested show unique and different biochemical characteristics and do not match the characteristics of the genus of the species being tested. Human error also occurs during the identification of bacteria and it takes a long time to find out the results of bacterial identification. The specific objective of the research is to produce an innovative GM3-Bacterial© application based on Android smartphones for bacterial identification. The research method is the GM3-bacterial© application initial display design and design prototype aplikasi GM3-bacterial©. The results showed that the design of the GM3-bacterial© application prototype design application had been successfully carried out. The GM3-Bacterial© application based on Android smartphones has been successfully designed using the Software suite for building GM3-bacterial© applications. The GM3-Bacterial© application is based on an Android smartphone for the identification of bacteria such as the recognition of morphology, biochemical properties, and types of bacteria.